2021
DOI: 10.1136/bmjgh-2020-003734
|View full text |Cite
|
Sign up to set email alerts
|

Is being a 'left-behind' child associated with an increased risk of self-poisoning in adulthood? Findings from a case–control study in Sri Lanka

Abstract: PurposeThe long-term consequences of parental emigration on offspring self-harm risk is unknown.MethodsWe investigated the association between experiencing parental emigration in childhood with hospital presentations for self-poisoning in adulthood using a hospital case–control study. Cases were adult self-poisoning patients (≥18 year olds) admitted to the medical toxicology ward Teaching Hospital Peradeniya, Sri Lanka. Sex and age frequency matched controls were recruited from the outpatient department or nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…To our knowledge, only 1 existing study investigated sex differences in the association of parental migration with NSSI. Knipe and colleagues 8 conducted a hospital-based case-control study and found no sex differences in self-poisoning behavior (the most common method of NSSI in Sri Lanka) between boys and girls with at least 1 parent who migrated, consistent with the findings of our study. Nonsuicidal self-injury for emotional regulation is closely associated with coping strategies, 38 and no sex differences have been detected for coping strategies.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…To our knowledge, only 1 existing study investigated sex differences in the association of parental migration with NSSI. Knipe and colleagues 8 conducted a hospital-based case-control study and found no sex differences in self-poisoning behavior (the most common method of NSSI in Sri Lanka) between boys and girls with at least 1 parent who migrated, consistent with the findings of our study. Nonsuicidal self-injury for emotional regulation is closely associated with coping strategies, 38 and no sex differences have been detected for coping strategies.…”
Section: Discussionsupporting
confidence: 90%
“…Four existing studies 8 , 9 , 10 , 11 have examined the association of parental migration with NSSI in children and adolescents with mixed conclusions or less convincing findings due to the use of an ambiguous definition of NSSI 8 or the failure to adjust for potential confounders. 9 , 10 , 11 In the present study, we used a validated diagnostic criterion for NSSI 19 , 28 , 29 and adjusted for up to 13 potential confounders, providing robust evidence that parental migration is independently associated with increased risk of less frequent NSSI among Chinese children, adolescents, and young adults and that those offspring who were left behind are at high risk for less frequent NSSI engagement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations